Poética e teoria da literatura na Roma Clássica - Wellington Ferreira Lima (2016)
It is taken as a dogma that the Poetics as a discipline is a term which has crystallized since, at least, the work of Aristotle and has been continued, later, by the work of Horace. There is also that the discipline we designate as Theory of Literature is far too recent, fixed by Wellek& Warrens work. In fact, a science of literature makes itself needed from the moment that literature has lost its place in the empirical world and ceased having its meaning by the context in which it was produced and by its effects in this reality. The poetics term arises in Aristotle (Met.;E.N.) as a way of knowledge to the man, opposing itself to the theoretical and the practical. When this tripartite division of perceiving the world is reduced to the opposition noscere x agere, thereis also the reconfiguration of the poets and poetrys places and, consequently, the production of a range of speeches on this manner, trying to handle what had already been within the strict scopeof tékhné. This work aims to comprehend how one of these speeches the poetry itself sets up the statutes of the poetic making in the tense time which extends from the end of the republic to the end of the Augustus governance, considered by the expert criticism as the golden age of Roman literature .